Identifying the Gray Zone between Bootleg and Counterfeit in the Context of Integrated Circuit Piracy in Indonesia - Cita Yustisia Serfiyani; Mieke Yustia Ayu Ratna Sari; Budi Hermono; Eny Sulistiyowati; Abhisek Kumar (Universitas Negeri Semarang, 2025)
Counterfeit integrated circuit (IC) products have been traded illegally in Indonesia due to a lack of public awareness of intellectual property rights (IPR) and inconsistent law enforcement. Irresponsible parties have produced fake ICs in the form of imitation goods, illegally imported from China to Indonesia—an issue that appears to be a further implication of the global technological trade war. Due to prohibited modifications, a gray zone exists between the classification of bootleg and counterfeit products, even though both are fake. Bootlegs are “inspired-products” protected by registered brands and industrial designs, which makes them more challenging to investigate than counterfeits that directly replicate the original. As a result, the proof aspects differ. It is essential to differentiate between counterfeits or bootlegs to enforce the appropriate sanctions and protect ICs in Indonesia. Using a normative research method, this legal research analyzes the differentiation between bootleg and counterfeit ICs and the legal protection of integrated circuits in Indonesia through statutory and conceptual approaches. This paper recommends the urgent need for a definitive classification to facilitate proof and the imposition of sanctions. Futhermore, the Indonesian government should revise Law No. 32 of 2000 by adding regulations regarding priority rights, enabling foreign IC rights holders to be better protected in Indonesia. Law enforcement efforts against counterfeit and bootleg ICs must also be supported by Indonesia’s commitment to participate in the Anti-Counterfeiting Trade Agreement.